Placenta Accreta in a Woman with Escherichia coli Chorioamnionitis with Intact Membranes - Emma M. Montelongo; Nathan R. Blue; Richard H. Lee (Case Reports in Obstetrics and Gynecology)
Background. Escherichia coli (E. coli) associated intrauterine infections with intact membranes are extremely rare. Case. A 30-year-old multiparous female presented at 26 weeks’ gestation with clinical signs of chorioamnionitis but physical examination suggested intact membranes. Her dietary history was concerned with Listeriosis. An amniocentesis was performed. Shortly thereafter, the mother developed septic shock and an urgent Cesarean delivery was performed. The patient required a peripartum hysterectomy for placenta accreta. Amniotic fluid cultures grew E. coli.